Reconstruction of Cropland for the Rikaze Area of China Since the Tubo Dynasty (AD 655) - Hongxia Pan; Qiong Chen; Zhilei Wu; Zemin Zhi; Wenguo Fang; Jiaqian Sun; Yanan Shi (Land)
The reconstruction of cropland across historical periods offers valuable insights into the relationship between climate change and human–environment interactions. By extracting key demographic and tax revenue data from historical documents, we estimated cropland data during the Tubo, Yuan, Ming, and Qing dynasties for the Rikaze area in China. Subsequently, according to the characteristics of cropland fragmentation in the Rikaze area, we employed geographically weighted regression (GWR) to reconstruct the 1 km × 1 km cropland cover datasets across the four dynasties for the Rikaze area. The findings are as follows. The amount of cropland showed that the change in cropland in the Rikaze area in the four periods was extremely high, which reflects the great instability of cropland in the Rikaze area. Under the combined action of social unification, cropland production policies, and a suitable climate, the Tubo dynasty was the most significant period of cropland development in the Rikaze area, with the area of cropland reaching 591,927 mu. However, under the influence of the nomadic regime and harsh climate in the Yuan dynasty, the cropland area was sharply reduced, reaching only 18,338 mu. During the Ming and Qing dynasties, the cropland area increased steadily, reaching 200,000 mu and 547,000 mu, respectively. The spatial distribution of cropland shows that the cropland in the Rikaze area is mainly distributed in the middle reaches of the Yarlung Zangbo River, the middle and lower reaches of the Nianchu River, and the Pengqu River Valley. Counties and districts with better agricultural conditions, such as Jiangzi, Bailang, and Renbu, are the main concentration areas of cropland in the Rikaze area. The overall spatial distribution pattern of cropland shows fragmented distribution along rivers, highlighting the characteristics of valley cropland. The research in this paper represents the active exploration of the reconstruction of cropland distribution under complex terrain conditions.